State Dominance in Myanmar : The Political Economy of Industrialization - Tin Maung Maung Than (Book collections on Project MUSE., 2007)
Focuses on the state's efforts to industrialize Myanmar, first through direct intervention and planning under a socialist economic framework as interpreted by the state leaders (1948-88) and lately (1989 onwards) through state-managed outward orientation.